Play Therapy with Ajining Dhiri Puppet Media to Improve Self-Esteem of Slow Learners - Pramudia Trisnani, Rischa; Hidayah, Nur; Ramli, M; Indreswari, Henny (KONSELOR, 2024)
This quasi-experimental study examines the effectiveness of play therapy using the Ajining Dhiri (ADHI) puppet medium to enhance self-esteem in slow learners. Utilizing a pretest-posttest control group design, the study involved 16 slow learners with low self-esteem, as measured by the Self-Esteem Inventory by Coopersmith (1978), validated (r=0.711–0.794) and reliable (Cronbach's alpha=0.760). Participants were divided into a treatment group receiving play therapy with ADHI puppets and a control group receiving standard group counseling. Data were analyzed using the Mann-Whitney U test. Baseline findings revealed that 50% of students scored low in Strength (recognition and respect), 62.5% moderate in Significance (acceptance and affection), 75% moderate in Virtue (ethical behavior), and 87.5% low in Ability (task performance). Post-intervention results demonstrated significant improvements in self-esteem across all indicators for the treatment group. The Mann-Whitney U test yielded a value of 0.000, Z = -5.093, and a p-value < 0.05, confirming a significant difference between the treatment and control groups. The play therapy sessions, structured in three phases, enabled students to explore self-expression and cognitive engagement through puppet interactions. Compared to the control group, students in the treatment group showed greater enthusiasm and consistent self-esteem improvements. These findings validate the alternative hypothesis (H1) that play therapy using ADHI puppet media effectively enhances self-esteem in slow learners, offering a culturally contextualized and engaging intervention for addressing their psychological needs.